The Role of Uncle (Atoin Amaf) in Belis Transactions on Wedding Customs - Melkianus Suni; Sanggar Kanto; Anif Fatma Chawa (Wacana Journal of Social and Humanity Studies, 2017)
This research is conducted to determine the Role of Uncle (Atoin amaf) in Belis Transaction in Marriage Culture of Naibenu mainly in Naibenu Sub district North Central Timor regency. The method used is qualitative method with the aim to descripe the role of Uncle in this belis transaction phenomenon in a natural manner and in as it is by using transcendental phenomenology approach namely the researcher puts aside any assumptions concerning the studied phenomena by conducting epoche that is containment initial knowledge so that the researcher is able to understand and describe any arising general meanings as well as any meanings behind the phenomena taken from life experiences of informants. The data collection technique is conducted by using in-depth interview by listening directly to any related informants. Also, the researcher conducted an observation to make sure the data validity obtained and conducted documentation in the forms of photographs and recorder records. Â The sample collection technique was by using Snow ball because the research has yet understood properly concerning the situation and location characteristics. Therefore, the researcher through new main informants was directed to main informants. Results of the research show that in belis payment process in marriage culture found in Naibenu, the one has the right to speak in decision making process is Uncle (atoin amaf) from the party of Bride. Om also serves as the marriage witness and guarantor from both bride and bridegroom.